Management of giant desmoid type fibromatosis of abdominal wall - Nikolić, Jelena; Marinković, Marija; Jovanović, Mladen; Tubić, Teodora; Tatalović, Vanja (Archive of Oncology, 2026)
Introduction. Desmoid type fibromatosis (DT) represents a rare benign tumor formations characterized with local aggressive behaviour, but absence of metastatic potential. Histologically they are often misdiagnosed leading to unnecessary radical surgery. Even with proper diagnose there are different approaches and not clear protocols for treatment of DT. Case report. The study presents the case of 33-year-old male that presented in emergency department with large swelling of abdominal wall that was present for two years. Ultrasound was done and abdominal swelling was described by radiologist as ventral hernia. After further radiological studies (CT scan and magnetic resonance) diagnosis of tumour of abdominal wall was established. Biopsy led to diagnose of sarcoma. Surgery was planned as tumour was growing rapidly reaching around 30 cm and producing necrosis of abdominal wall skin. After resection of 8.5kg of tumour and clinically clear margins defect was reconstructed by placing polypropylene mesh and darn Nylon suture with local rotational skin flap. In the postoperative days an infection of surgical wound developed. Infection was resolved in two weeks without further complications. The definitive histopathological diagnoses was desmoid type fibromatosis. Conclusion. Active surveillance is considered today as most acceptable strategy in treatment of DT. Better understanding of genetic alterations which are in base of DT and determining prognostic factors that favour aggressive behaviour, will lead to creation of appropriate individual strategy and tailored therapy for every patient.
Keywords: Desmoid tumor; abdominal wall; agressive; fibromatosis; reconstruction; case report